Distributed Heat Supply for Distillation Control to Reduce Feed Composition Disturbance Effects. Issue 12 (29th October 2013) - Marangoni, C.; Machado, R. A. F.; Bolzan, A.
Abstract The introduction of heat in stages combined with a reboiler as a distillation control strategy is proposed aiming to reduce the transition time when a feed composition disturbance occurs. This is the most severe type of perturbation and results in long transition times which are economically undesirable. Experiments were carried out in a pilot distillation column with ethanol and water for testing two different control strategies: conventional, i.e., using both last stage and reboiler temperature controllers, and distributed, i.e., conventional strategy plus stage temperature controllers. The results with this operational approach indicated a significant reduction in the time required for the column to stabilize when compared with the conventional approach. The proposed strategy proved to be a viable alternative, enabling faster dynamics and smaller volumes to be processed outside the predefined quality parameters.